The Role of Purchase Intention in Mediating the Impact of Digital Marketing Strategies on Online Shopping Behavior: A Case Study of Fashion Product Consumers in SMEs. - Dirgantini, Devi; Haryono, Tulus (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
In recent years, the issues reveals that millennial interest in purchasing SMEs fashion products has declined in the digital era. This study aims to explores millennial enthusiasm for buying SMEs fashion products amidst the proliferation of digital marketing strategies like live streaming, sales promotions, and celebrity endorsements. Using convenience sampling, the study gathered data from 134 respondents in Central Java through an online survey. The analysis, conducted with Structural Equation Modeling (SEM) and Partial Least Squares (PLS) using SmartPLS 3. The results indicate a positive relationship between purchase intention, celebrity endorsements, and sales promotions towards online shopping behavior. However, live streaming did not directly impact online shopping behavior but had a positive and significant influence through purchase intention. Meanwhile, celebrity endorsements and sales promotions do not have a positive and significant impact on online shopping behavior through purchase intention. The implications of this study suggest that SMEs need to better leverage relevant digital marketing strategies to enhance consumer purchase intentions.